Red-Emitting Coatings for Multifunctional UV/Red Emitting LEDs Applied in Plant Circadian Rhythm Control - Bispo, Airton G. [UNESP]; Lima, Sergio A. M. [UNESP]; Carlos, Luís D.; Ferreira, Rute A. S.; Pires, Ana M. [UNESP] (The Electrochemical Society, 2020)
Multifunctional light-emitting diodes (LEDs) formed by coating deep-UV-emitting (<300 nm) LED chips with downshifting phosphors are of great interest for applications in indoor farms as both antibacterial (UV radiation) and photosynthetic agent (red light). Challenges include the fabrication of high-brightness downshifting converter films with controlled thickness excited in the deep-UV spectral region. We address it by optimizing the amount of Ba2SiO4:Eu(III) red-emitting phosphor dispersed in poly (methyl)methacrylate (PMMA), yielding luminescent films with tunable thickness. Taking advantage of the intra-4f6 transitions, the Eu(III) luminescence is used as local probe, pointing out the presence of 8 non-equivalent local sites for the lanthanides. PMMA enables the processing of flexible films and simultaneously acts as a selective filter to deep-UV radiation, controlling the amount of UV radiation for indoor farm applications. Moreover, after the dispersion in PMMA, the Eu(III)-based luminescence remains analogous to that of the isolated phosphor with an absolute emission quantum yield of 0.11 ± 0.01, confirming that Ba2SiO4:Eu(III)/PMMA films display desirable features to be used as coatings of deep-UV emitting LEDs toward multifunctional devices for indoor farm application.